DISCRRACY CONCEPT IN LITHUANIAN PUBLIC LAW - Bakševičienė, Rūta (Teisė, 2017)
The article analyzes variations of the concept of discretion used in contemporary Lithuanian public law, the content for this term. The article uses the practice of administrative courts as an illustrative part of public law. It also analyzes the discretion in legislation, issues of the limits of discretion of officials, judges, and the activities of law-making subjects. The article also highlights the aspects of the right of discretion when adopting individual and regulatory legal acts.